Synthesis, docking study, and pharmacological evaluation of S-acetamide derivatives of 4,6-dimethyl-2-thiopyrimidine as anticonvulsant agents - Hanna Ivanivna Severina, Olha Olegivna Skupa, Natalya Ivanivna Voloshchuk, Victoriya Akopivna Georgiyants (Journal of Applied Pharmaceutical Science, 2020)
The aim of this study is the direct synthesis of new (4,6-dimethylpyrimidin-2-yl)thio-N-acetamides derivatives as possible anticonvulsants. The interaction of thiourea with acetylacetone in sodium ethoxide resulted in the scaffold of 4,6-dimethyl-2-thiopyrimidine. Thioacetamide derivatives were synthesized by alkylation of 4,6-dimethyl-2- thiopyrimidine with comparable α-chloroacetamides in the Dimethylformamide (DMF) environment and in the presence of Ðš2Ð¡Ðž3. The methods of 1H and 13C Nuclear magnetic resonance (NMR) spectroscopy, Liquid chromatography– mass spectrometry (LS/MS), and elemental analysis established the structure of the synthesized compounds. The affinity of the studied compounds with anticonvulsant biotargets— Type-A γ-aminobutyric acid receptor (GABAAR) and the gamma-aminobutyric acid-aminotransferase enzyme—was carried out using the molecular-docking method. The highest affinity was predicted for the compound having 4-bromophenyl substituent: −7.0 (GABAA) and −8.0 (GABAÐÐ¢) kcal/mol. Nevertheless, all the studied compounds conceded to the reference ligands—phenobarbital (−7.6 kcal/mol) and vigabatrin (−9.0 kcal/mol). The model of pentylenetetrazole-induced seizures in rats has shown that the studied compounds have moderate anticonvulsant activity. 4-Bromophenyl acetamide has also shown the most pronounced activity: the substance statistically significantly extended the latency period and reduced the duration of seizures by 3.4 and 2.2 times, respectively; moreover, it reduced lethality of the laboratory animals by 80% and by 2.5 times severity of seizures. Correspondence between the docking results and in vivo studies, using PTZ-induced seizures, as well as some parameters of “structure-anticonvulsant activity” correlation, was determined.
Keywords: 2-thiopyrimidine, docking, GABA, anticonvulsant activity.